FEM analysis of residual stress induced by repair welding in SUS304 stainless steel pipe butt-welded joint. (October 2020) - Dai, Peiyuan; Wang, Yifeng; Li, Suo; Lu, Shijie; Feng, Guangjie; Deng, Dean
Graphical abstract: Highlights: The residual stress of repaired thick pipe joints was numerically studied. The variation of welding residual stress induced by repair was discussed. The increase in repair length has little effect on the peak of tensile stress. Abstract: Repair welding is widely used to repair defects such as fatigue crack and stress corrosion crack in metal structures for prolonging their service lives. However, the residual stress induced by repair welding potentially threatens the safety of the repaired weldments, especially stainless steel pipe structures and pressure vessels used in nuclear power plants. Based on the MSC. Marc software, a thermal elastic plastic finite element method with the consideration of full 3-D model, moving heat source and advanced material model was developed to simulate residual stress distribution induced by repair welding. In the current study, the effectiveness of the developed computational approach was verified by a two-pass thin-walled butt-welded SUS304 steel pipe mock-up at first. Then, the residual stress distributions in a medium thickness SUS304 steel pipe butt-welded joint before and after repair welding were investigated numerically. The simulation results show that the peak value of axial residual stress after repair welding was significantly increased, while the variation of the maximum value of hoop residual stress was limited. In addition, the effect of repair length on the feature of residual stress distribution was studied numerically. The numerical results indicate that the peak value of repair-induced residual stress decreases with the repair length. The main reason is that the longer the repair welding length is, the less local constraint will be. The residual stress distribution in the repair area at service temperature was also discussed in this study. The results obtained from the current study will be helpful in evaluating the structural integrity of repaired weldments.